Replantation of an Amputated Hand- A Landmark surgery with Multidisciplinary Team Approach - Islam, ASM Shariful; Shahidullah, AYM; Mostofa, Md Golam; Hossain, Md Daud (Cardiovascular Journal, 2022)
An amputation of the hand is a disastrous traumatic injury especially for advanced machinery workers which adversely affects the victim’s ability to earn a livelihood, support a family, and carry out daily activities. It also produces great psychological impact. In the following case report, we described a middleaged male with an amputation at the level of the distal forearm who underwent replantation. The transfer of the amputated hand, operative technique and postoperative status are described. Awareness of the possibility of salvage should be spread among healthcare providers and the need for immediate attention by a multispecialty team is advocated. This report reviews the literature related to the operative technique, contraindications and long-term results. Cardiovasc j 2022; 15(1): 106-110